Pemanfaatan Sampah Plastik sebagai Pendukung Perkembangan Industri Kreatif Nasional - Zerimah Afgani Hasibuan; Riyanto Riyanto (STIT Sirojul Falah Bogor, 2023)
Public awareness of the environment is still lacking so that a lot of waste pollutes the environment, one of which is plastic waste. Plastic waste is waste that is difficult to decompose, so to reduce plastic waste, it must be recycled. Actually, the problem of plastic waste can be overcome, one of which is through the creative industry. Creative industries can be started through community activities as a group or individually to process plastic waste into something more useful. Unused plastic waste can be reused through community creativity and can also provide additional economic benefits for the community. This can be done by processing waste plastic into useful and valuable handicrafts. The development of creative industries can be supported by community creativity and government training. With the use of plastic waste through the creative industry, it is hoped that the community can reduce the problem of plastic waste that pollutes the environment and can improve the economy through people's creative ideas to process plastic waste to make it more useful. Keywords: Plastic waste, Creative Industry, Community